TEMPERATURE EFFECTS ON CORM GERMINATION AND FLOWERING OF CROCUS SATIVUS L. (SAFFRON) - Nordiyanah Anuar; Rosna Mat Taha; Sakinah Abdullah; Melanova Nazira; Misirova Surayyo Abdumutalovna (Journal of Animal and Plant Sciences, 2024)
Climate change has hindered Crocus sativus production since its early phases of development are vulnerable to temperature stress. Indoor cultivation of C. sativus in Malaysia is strongly encouraged as it provides optimum plant growth without being impacted by unfavourable weather or geographical limitation. The present study aims to investigate the effects of temperatures on corm germination and flowering of Crocus sativus in a controlled environment. Saffron, a spice derived from the flower of C. sativus is the world’s most expensive spice and is native to the Mediterranean region. Three different temperatures (10°C, 23°C and 30°C) were tested for corm germination while the flowering process was tested in the temperature of 16°C, 23°C or 30°C using a randomized complete block design (RCBD). The results showed that C. sativus required a specific temperature setting and developed best in a sequence of high temperature during corm germination to a lower temperature during flower initiation. The optimum temperature for flower formation was 16°C provided that the corms were germinated at a higher temperature in the range of 23°C to 30°C. The results provide valuable information for the cultivation of C. sativus as a new prospect for Malaysia’s economy, considering its high commercial and medicinal value.
Keywords: Corm; Crocus sativus; Malaysia; Saffron; Temperature